Evolution of the oxyhemoglobin dissociation curve in COVID-19 related ARDS patients - Dalne, Charlotte; Biston, Patrick; Piagnerelli, Michaël (Frontiers in Physiology, 2024)
IntroductionSevere hypoxemia is the leading cause of admission in intensive care (ICU) in patients with COVID-19 related acute respiratory distress syndrome (ARDS). In these patients, several studies reported a left shift of the oxyhemoglobin dissociation curve associated with a lower mortality. However, these results are conflicting, as these studies include few patients and often no control groups. Moreover, the calculation of P50, representing the PaO2 value at which 50% of hemoglobin is saturated, is not corrected for factors known to influence it (pH, PaCO2 or temperature). For all of these reasons, we compared the corrected P50 between ICU patients with severe COVID-19 related ARDS on mechanical ventilation or not, and ARDS from other causes. We investigated the evolution of the corrected P50 during the first 3 days of ICU and its relationship with ICU mortality.Methods and PatientsWe retrospectively calculated the corrected P50 in three groups of patients: intubated and mechanically ventilated COVID-19 related ARDS, non-intubated COVID-19 related ARDS and intubated patients with ARDS due to other infectious causes. The corrected P50 was calculated, on the worst blood gas analysis on days 1 and 3 of ICU admission, by the formula of Hill but modified by Dash et al., controlled for pH, PaCO2 and temperature. We collected ICU mortality.Results463 blood gas analysis at days 1 and 3 from 214 ICU COVID-19 related ARDS patients (114 with intubation and 100 without) and 35 ICU patients with ARDS from other causes were analyzed. All patients were severely hypoxemic: PaO2/FiO2 of 76 [58-108] mmHg for intubated COVID-19, 79 [60-108] mmHg for non-intubated COVID-19 and 142 [78-197] mmHg for the third group (p < 0.001). The mortality rate was higher in intubated COVID-19 related ARDS patients (44.7 versus 14 versus 37% in ARDS from other causes; p < 0.001). The corrected P50 was significantly lower in COVID-19 patients, especially in non- intubated patients (21.2 [18.8–25.2] mmHg vs. 25.5 [19.2–30.3] mmHg in intubated patients; compared to ARDS from other causes: 27.2 [23.3-35.4] mmHg; p < 0.001. The corrected P50 does not change over the first 3 days, except for the non intubated COVID-19 related ARDS and is not correlated with ICU mortality (odds ratio = 0.98 [0.95-1.03]; p = 0.51), in contrast of PaO2/FiO2 and ICU gravity scores.ConclusionThe oxyhemoglobin dissociation curve at ICU admission was left shifting in severe COVID-19 related ARDS patients regardless of the type of ventilation. This deviation increases the third day only in non-intubated COVID-19 related ARDS and was not related to the outcome.